VD_FINDINFO LAVAM 2/09 - 18/2009 vom 9. Oktober 2009 - VD Tribunal cantonal (2009)
RÉDUCTION DES PRIMESAM, REVENU DÉTERMINANT | 11 LVLAMal, 12 LVLAMal, 9 LVLAMal, 17 RLVLAMal, 23 al. 2 let. e RLVLAMal